2018
DOI: 10.21826/2446-8231201873106
|View full text |Cite
|
Sign up to set email alerts
|

Potential herbicidal effect of synthetic chalcones on the initial growth of sesame, Sesamum indicum L., and brachiaria, Urochloa decumbens(Stapf) R. D. Webster

Abstract: The search for and identifi cation of new molecules for the development of herbicides has grown in recent decades. With the objective of developing effi cient, environmentally friendly herbicides, we evaluated the phytotoxic activity of 13 synthetic chalcones on the development of sesame Sesamum indicum L. and brachiaria Urochloa decumbens (Stapf) R.D. Webster. Growth experiments were conducted at 30°C within a photoperiod of 12 hours. The positive control was distilled water whereas the negative control was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In terms of unreactive groups, we found that certain substituents, such as CH 3 , CF 3 , OCH 3 , isopropyl, isopropoxy, NO 2 , and halo groups, showed very low inhibitory activity toward tested plants. This was similar to Gomes’s work 37 that, among their 13 synthesized chalcones, simple trans -chalcone (Figure 1) was the most active compound against the initial growth of sesame ( Sesamum indicum L.) and brachiaria ( Urochloa decumbens (Stapf) R. D. Webster). Other chalcones bearing either electron-donating groups (OH, N(CH 3 ) 2 , or OCH 3 ) or electron-withdrawing groups (NO 2 or Cl) showed only low to moderate effects.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In terms of unreactive groups, we found that certain substituents, such as CH 3 , CF 3 , OCH 3 , isopropyl, isopropoxy, NO 2 , and halo groups, showed very low inhibitory activity toward tested plants. This was similar to Gomes’s work 37 that, among their 13 synthesized chalcones, simple trans -chalcone (Figure 1) was the most active compound against the initial growth of sesame ( Sesamum indicum L.) and brachiaria ( Urochloa decumbens (Stapf) R. D. Webster). Other chalcones bearing either electron-donating groups (OH, N(CH 3 ) 2 , or OCH 3 ) or electron-withdrawing groups (NO 2 or Cl) showed only low to moderate effects.…”
Section: Resultssupporting
confidence: 88%
“…However, to the best of our knowledge, the weed control ability of flavokawains and related chalcones has not yet been investigated. Even though the herbicidal activities of some simple trans -chalcones (or 1,3-diphenyl-2-propen-1-one) (Figure ) have been reported, there is a small variety of substituents on the rings of tested chalcones. Therefore, more work is needed to explore the chemical clues that provide herbicidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…U. decumbens as a target species usually shows low sensibility to many compounds in phytotoxic bioassays. , In this sense, the results shown here for U. decumbens may be due to the great intrinsic variability of its seeds and its resistance to phytotoxic compounds.…”
Section: Resultsmentioning
confidence: 69%
“…This research includes the development of Sesamum indicum L. and Urochloa decumbens (Stapf) R.D. Webster, [30] the inhibition of phosphoenolpyruvate carboxylase, which is an essential enzyme for carbon fixation and biomass increment, [31] the inhibition of p ‐hydroxyphenylpyruvate dioxygenase and tyrosine amino transferase of Lemna paucicostata and Arabidopsis thaliana plants, [32] along with the evaluation of galactosyl‐conjugated furylchalcones for plant growth regulation in Leptochloa chinensis (L.) Nees, Echinochloa crus‐galli (L.) Beauv., and Amaranthus tricolor L [33] …”
Section: Introductionmentioning
confidence: 99%
“…This research includes the development of Sesamum indicum L. and Urochloa decumbens (Stapf) R.D. Webster, [30] the inhibition of phosphoenolpyruvate carboxylase, which is an essential enzyme for carbon fixation and biomass increment, [31] the inhibition of p-hydroxyphenylpyruvate dioxygenase and tyrosine amino transferase of Lemna paucicostata and Arabidopsis thaliana plants, [32] along with the evaluation of galactosyl-conjugated furylchalcones for plant growth regulation in Leptochloa chinensis (L.) Nees, Echinochloa crus-galli (L.) Beauv., and Amaranthus tricolor L. [33] In a previous study, our research group described the phytotoxicity of chalcone derivatives, demonstrating that (E)chalcone derivatives reduced electron transport on PSII and acted as a post-emergent herbicide, thereby reducing the biomass accumulation of Ipomoea grandifolia plants. [34] The aims of current work are the synthesis of an array of fluorinated chalcone derivatives, evaluation and determination of the effects of these compounds on photosynthetic apparatus, and pre-and post-emergence herbicide activities.…”
Section: Introductionmentioning
confidence: 99%